Measurement of longitudinal dispersion in streams and its application using a water quality model - Te, Shu Harn; Mohamed, Maketab (2003)
QUAL2E is one of the most widely used water quality model for watershed and stream management. It is capable of estimating the wasteload allocation or total maximum daily load (TMDL) for a given stream or river. The predictive equations used in QUAL2E were developed in United States and England; therefore, the applicability of QUAL2E in Malaysia with different climatological and geological conditions needs to be studied. In modeling, the accuracy of simulation is highly dependent upon the accuracy of empirical coefficients used, such as longitudinal dispersion. In this study, a water quality model upstream of Tebrau River was calibrated. The accuracy of the use of default dispersion constant, K (dimensionless), in water quality model (QUAL2E), for predicting the longitudinal dispersion effect of stream was examined. Longitudinal dispersion coefficients also calculated from predictive equations. Finally, an error analysis was conducted to compare the standard error (SE) of model outputs resulted from different longitudinal dispersion coefficients and evaluated which method gave the best result.